Advancing business process management lifecycle implementation through the integration of the design for Six Sigma method - Kovach, J.; Cardoso-Grilo T; Kalakou, S.; Martins, A. (Business Process Management Journal, 2024)
Purpose This research proposes how Design for Six Sigma (DFSS) provides a complementary approach for business process management (BPM) lifecycle implementation in order to address gaps identified in the current literature. Design/methodology/approach The mandatory elements of a method (MEM) framework is used to illustrate DFSS's maturity as a process redesign method. The use of DFSS in a BPM context is described through several action research case examples. Findings This research specifies the procedure model (order of development activities), techniques, results, roles and information/meta model (conceptual data model of results) associated with using DFSS to address BPM-related challenges. The action research case examples provided discuss the details of implementing BPM using DFSS to design, implement and test redesigned processes to ensure they fulfill the needs of process participants. Research limitations/implications While the case examples discussed were performed in only a few settings, which limits the generalizability of their results, they provide evidence regarding the wide range of domains in which the proposed DFSS-BPM approach can be applied and how the tools are used in different contexts. Practical implications This research offers a road map for addressing the challenges practitioners often face with BPM lifecycle implementation. Originality/value This research provides the first attempt to integrate DFSS as a complementary method for BPM lifecycle implementation.